Classifying the performance of judo techniques in athletes with visual impairments during official competitions - Lima Kons, R.; Henríquez, M.; Detanico, D. (Perceptual and Motor Skills, 2025)
Classifying judo technique performance offers valuable insights into the technical-tactical profiles of judo athletes with visual impairment, particularly in high-level competition. This approach allows for a deeper understanding of how visual impairments influence the execution of specific techniques, which can vary across athletes` sex, sport classes and weight categories. In this regard, this study aimed to analyze the technical profiles of judo athletes with visual impairments by applying a technique-specific classification system across the London 2012, Rio 2016, and Tokyo 2020+1 Paralympic Games, while accounting for sex, sport class, and weight category. Data were extracted from the official results books of the London 2012, Rio de Janeiro 2016 and Tokyo 2020+1 Paralympic Games, covering matches from seven male and six female weight categories, totaling 380 athletes and 522 matches. Throwing and groundwork techniques were classified according to a technique-specific classification system. Chi-Square tests were used to test the associations between groups of techniques and sex, sport class (B1, B2 and B3), and weight category with a significant level set at p < .05. Significant associations were found between technique classifications and sex (x2 = 34.49, p < .001), sport class (x2 = 26.16, p = .046) and weight category (x2 = 123.52, p < .001). Groundwork techniques showed higher usage across all categories analyzed. The findings underscore the importance of understanding the technical profiles of judo athletes with visual impairments and their specific needs. These insights contribute to favor better training strategies and competition preparation tailored to the unique requirements of judo athletes with visual impairments.